Clontuskert Augustinian Priory, rood screen, capital - O'Donovan, Danielle (My University, 2008)
Capital of rood screen, from top down moulding comprises: scroll, roll, angle-fillet, scroll with upper and lower fillets, bell with keel, necking-scroll. This capital is very similar to those from the cloister at Holycross and the group related to it - particularly the use of the scroll, roll and angle-fillet in the upper element and the keel in the bell.
Rood screen
Keywords: scroll; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Gothic capitals (Architecture); Late Medieval; roll moldings; fillets (moldings); keel moldings; bell capitals